Histological evolution of pleuroparenchymal fibroelastosis. Issue 4 (23rd December 2014) - Hirota, Takako; Yoshida, Yuji; Kitasato, Yasuhiko; Yoshimi, Michihiro; Koga, Takaomi; Tsuruta, Nobuko; Minami, Masato; Harada, Taishi; Ishii, Hiroshi; Fujita, Masaki; Nabeshima, Kazuki; Nagata, Nobuhiko; et al.
<x xml:space="preserve">Abstract</x> Aims To investigate the histological evolution in the development of pleuroparenchymal fibroelastosis (PPFE). Methods and results We examined four patients who had undergone surgical lung biopsy twice, or who had undergone surgical lung biopsy and had been autopsied, and in whom the histological diagnosis of the first biopsy was not PPFE, but the diagnosis of the second biopsy or of the autopsy was PPFE. The histological patterns of the first biopsy were cellular and fibrotic interstitial pneumonia, cellular interstitial pneumonia (CIP) with organizing pneumonia, CIP with granulomas and acute lung injury in cases 1, 2, 3, and 4, respectively. Septal elastosis was already present in the non‐specific interstitial pneumonia‐like histology of case 1, but a few additional years were necessary to reach consolidated subpleural fibroelastosis. In case 3, subpleural fibroelastosis was already present in the first biopsy, but only to a small extent. Twelve years later, it was replaced by a long band of fibroelastosis. The septal inflammation and fibrosis and airspace organization observed in the first biopsies were replaced by less cellular subpleural fibroelastosis within 3–12 years. Conclusions Interstitial inflammation or acute lung injury may be an initial step in the development of PPFE.